Avaliação de diferentes cultivares de Panicum maximum no semiárido sergipano - Souza, Laís Santos (2024)
The aim was to assess the productive performance of different cultivars of Panicum maximum in semi-arid conditions. The experiment took place at the Embrapa Semi-Arid experimental farm in Mesinhas, Nossa Senhora da Glória-SE, during 2019. The experimental area, 0.43 ha (4,324 m²), was divided into useful plots of 60 m² (6.0 x 10.0 m) with 4.0 m corridors. A randomized block design with three replications was used during the dry period. Seven Panicum maximum cultivars (Mombaça, Tanzania, Massai, Aruana, BRS Zuri, BRS Tamani, and BRS Quênia) were tested. No statistical differences were observed among cultivars for leaf dry weight (LDW), stem dry weight (SDW), and total dry weight (TDW). However, Massai grass showed higher values for dead material dry weight (DMDW), while Mombaça had lower values. Mombaça cultivar exhibited the highest %Leaf, while Massai had the lowest %Leaf. %Stem was higher in Tamani and lower in Quênia cultivar. Massai had the highest %Dead Material, while Tamani and Mombaça had the lowest. All cultivars showed heights exceeding the recommended. The leaf/stem ratio (L/S) was higher in Quênia, and Mombaça, Tamani, Tanzania, and Zuri had higher final leaf size (FLS) values. Only Tanzania cultivar showed superiority in final stem size (FSS). The green material/dead material ratio (GM/DM) showed no statistical differences. Regarding tiller population density (TPD/m²), Aruana and Massai were superior and equal to each other. It is concluded that the Mombaça cultivars performed better in the semi-arid conditions of Sergipe..